Phytochemical screening and antipyretic effects of hydro-methanol extract of Melia azedarach leaves in rabbits (Bangladesh Journal of Pharmacology, 2013)
The antipyretic effect of the hydro-methanol extract of Melia azedarach leaves was investigated using the yeast induced pyrexia method in rabbits. Paracetamol was used as a positive control and negative control group received distilled water. Rectal temperatures of all rabbits were recorded immediately before the administration of the extract or vehical or paracetamol and again at 1 h interval for 6 h using digital thermometer. The extract was also phytochemically screened for alkaloids, tannins, saponins, flavonoids, cardiac glycosides and phenols. At 500 mg/kg dose the extract showed significant (p